Clinical implications of measuring prolactin levels in males of infertile couples. (22nd August 2013) - Lotti, F.; Corona, G.; Maseroli, E.; Rossi, M.; Silverii, A.; Degl'Innocenti, S.; Rastrelli, G.; Forti, G.; Maggi, M.
Summary: Although in females of infertile couples abnormal prolactin (PRL) has a definitive role in the medical flowchart, its role in males is less clear. Animal models suggest that PRL does not play a major role in male reproduction, although its trophic action on male accessory glands was often observed. Studies in humans are scanty. We systematically evaluated possible clinical and ultrasound correlates of PRL in males of infertile couples. Of 288 consecutive males of infertile couples, 269 (36.6 ± 4.4 years) without genetic abnormalities were studied. All men underwent physical, biochemical, seminal evaluation and scrotal and transrectal ultrasound before and after ejaculation. Ejaculatory and erectile functions were assessed by Premature Ejaculation Diagnostic Tool (PEDT) and International Index of Erectile Function (IIEF)‐15 respectively; prostate‐related symptoms by National Institutes of Health‐Chronic Prostatitis Symptom Index and International Prostate Symptom Score; psychological symptoms by Middlesex Hospital Questionnaire. Among semen parameters, only the positive association between PRL and ejaculate volume was significant, even adjusting for age, total testosterone and thyroid‐stimulating hormone (adj. r = 0.126, p < 0.05). In a logistic ordinal model, adjusting for the aforementioned confounders and ejaculate volume, PRL was negatively associated with delaying ejaculation according to PEDT#1 score (Wald = 4.65, p < 0.05). In an age‐ and ejaculate volume‐adjusted, iterative binary logistic model, low PRL was associated with a fivefold risk of any failure in controlling ejaculation (HR = 5.15 [1.15–23], p < 0.05). Among scrotal and transrectal ultrasound features, we found a significant positive association between PRL and seminal vesicles (SV) volume and inhomogeneity, before and after ejaculation, and with deferential ampullas diameter. Associations with PRL were confirmed in nested 1 : 1 case–control analysis. No significant associations were found between PRL and other clinical parameters. For the first time, this study extends the concept of a trophic effect of PRL on male accessory glands from animals to humans. We report a positive association among PRL and ejaculate and SV volume, before and after ejaculation. Low PRL is associated with a lessened ability to control ejaculation.